RESULTS OF APPROBATION OF THE UNIFIED METHODOLOGY FOR COMPREHENSIVE ASSESSMENT OF THE QUALITY OF DECENTRALIZED DRINKING WATER SOURCES IN A LARGE AGRO-INDUSTRIAL REGION (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The present study is devoted to the development and validation of a unified methodology for integrated geo-ecological diagnostics of the state of sources of decentralized domestic drinking water use. The Voronezh region with a population of 2.285 million people and a developed industrial-agrarian structure of the economy was chosen as a model region. The proposed methodology is based on a set of scientific and methodological approaches to the collection, analysis, processing and presentation of information on the quality of drinking water, levels of environmental risks to public health based on the methods of probabilistic-statistical analysis of eco-geodata, geoinformation modeling and mapping technologies.
Keywords: priority pollutants; decentralised water sources; drinking water quality; administrative areas; health risk assessment